Genome-wide analysis of translational efficiency reveals distinct but overlapping functions of yeast DEAD-box RNA helicases Ded1 and eIF4A - Sen, Neelam Dabas; Zhou, Fujun; Ingolia, Nicholas T.; Hinnebusch, Alan G.

(untitled) (Genome Research, 2015)
DEAD-box RNA helicases eIF4A and Ded1 are believed to promote translation initiation by resolving mRNA secondary structures that impede ribosome attachment at the mRNA 5′ end or subsequent scanning of the 5′ UTR, but whether they perform unique or overlapping functions in vivo is poorly understood. We compared the effects of mutations in Ded1 or eIF4A on global translational efficiencies (TEs) in budding yeast Saccharomyces cerevisiae by ribosome footprint profiling. Despite similar reductions in bulk translation, inactivation of a cold-sensitive Ded1 mutant substantially reduced the TEs of >600 mRNAs, whereas inactivation of a temperature-sensitive eIF4A variant encoded by tif1-A79V (in a strain lacking the ortholog TIF2) yielded <40 similarly impaired mRNAs. The broader requirement for Ded1 did not reflect more pervasive secondary structures at low temperature, as inactivation of temperature-sensitive and cold-sensitive ded1 mutants gave highly correlated results. Interestingly, Ded1-dependent mRNAs exhibit greater than average 5′ UTR length and propensity for secondary structure, implicating Ded1 in scanning through structured 5′ UTRs. Reporter assays confirmed that cap-distal stem–loop insertions increase dependence on Ded1 but not eIF4A for efficient translation. While only a small fraction of mRNAs shows a heightened requirement for eIF4A, dependence on eIF4A is correlated with requirements for Ded1 and 5′ UTR features characteristic of Ded1-dependent mRNAs. Our findings suggest that Ded1 is critically required to promote scanning through secondary structures within 5′ UTRs, and while eIF4A cooperates with Ded1 in this function, it also promotes a step of initiation common to virtually all yeast mRNAs.